Ateso Grammar: A descriptive account of an Eastern Nilotic Language - Barasa, David (Linguistics, 2017)
This study discusses the structure of Ateso, an Eastern Nilotic language. Based on interview and recorded data from fieldwork conducted in both Uganda and Kenya, where Ateso is spoken, the study provides the first comprehensive description of the phonology, morphology and syntax of the language. The main findings of this study are as follows: The key feature of Ateso's phonological structure is that vowel alternation strategies are constrained by three harmony rules: root-control, feature-control, and, finally, mid-vowel assimilation. While Ateso shares this structure with the other Eastern Nilotic languages, it has its unique features as well. For example, while the other members of the Eastern Nilotic family have lost the vowel */ä/, Ateso has retained it phonetically. Ateso's noun morphology has noun-inflectional affixes associated with gender- and number marking. The language employs noun prefixes for gender and uses suffixes to express number and to derive words from others. With regard to its verbal morphology, Ateso verb forms are inflected for a variety of functions. Inflectional categories such as person, number, tense, aspect and mood are marked on the verb either segmentally or supra-segmentally. Tense is expressed suprasegmentally by tone on the nucleus of verb roots, while different morphemes mark person, number, aspect and mood. The discussion of Ateso verb morphology covers verbal derivations and extensions; namely, causatives, ventives, itives, datives, iterative, passives and instrumentals. Regarding its syntactic structure, as a VS/VO language, Ateso allows for a complete clause made up of an inflected verb only, or an inflected verb followed by one or two NPs/or an NP and a pronoun. The language can also have sentence structures involving strategies such as coordination, subordination and clause chaining.